Osteoblast interactions with various hydroxyapatite based biomaterials consolidated using a spark plasma sintering technique - Kumar, R. (2012)
This study investigated the osteoblast behaviors on various hydroxyapatite based biomaterials that were consolidated at 1100°C for 3 min by a spark plasma sintering technique. The osteoblasts from human fetal osteoblast cell line were cultured in the medium on the various biomaterials surfaces (HA, RF21, 1SiHA, and 5SiHA) to assess the cell morphology and proliferation as well as cell differentiation (alkaline phosphatase activity). Moreover, the bone -carboxyglutamic protein or osteocalcin in the medium were determined at different periods of culture. The present results indicated that the amount of osteocalcin in the medium decreased during the periods of culture. The highest osteocalcin production obtained from the biomaterial 5SiHA after cell culture for 2 days demonstrated that the presence of silica in the biomaterials enhanced the cell differentiation by the rapid release of silicate and calcium ions.